Pembentukan Karakter Peserta Didik Melalui Budaya Islami di SMPN 1 Tangse Pidie - Cut Ela Safira; Sri Rahmi; Nurussalami (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
Character building is an effort to develop character, especially in students with education, so that good character values are formed, especially with Islamic culture in schools to overcome moral crises. This study aims to determine the principal's strategy in building student character through Islamic culture at SMPN 1 Tangse Pidie, to find out the process of forming student character through Islamic culture at SMPN 1 Tangse Pidie and to find out the obstacles to student character building through Islamic culture at SMPN 1 1 Tangse Pidie. This study uses a qualitative method with a descriptive approach. The subjects in this study were school principals, student assistants, religious teachers and students at SMPN 1 Tangse Pidie. Based on the results of the study, it was found that: 1) The principal's strategy in building the character of students through Islamic culture has been well implemented. Moral modeling strategies, advice strategies and habituation strategies are the most widely applied in SMPN 1 Tangse Pidie, 2) The process of forming the character of students through Islamic culture is carried out by involving students actively in learning, based on individual differences, namely in terms of giving directions and coaching to students, linking theory with practice while studying, developing communication and collaboration in learning, increasing students' courage, increasing learning and adapting lessons to concrete operational levels and 3) Barriers to the formation of students's character through Islamic culture including the family environment, environment and school environment.